Promoting Health in Virtual Worlds: Lessons From Second Life - Suomi, Reima; Mäntymäki, Matti; Söderlund, Sari (JMIR Publications, 2014)
BackgroundSocial media services can help empower people to take greater responsibility for their health. For example, virtual worlds are media-rich environments that have many technically advantageous characteristics that can be used for Health 2.0 purposes. Second Life has been used to build environments where people can obtain information and interact with other users for peer support and advice from health care professionals. ObjectiveThe intent of the study was to find out whether Second Life is a working and functional platform supporting the empowerment of people in health-related issues. MethodsWe conducted a review of the current health-related activity in Second Life, coupled with an extensive series of observations and interactions with the respective resources inside Second Life. ResultsA total of 24 operative health resources were found in Second Life, indicating that health-related activity is rather limited in Second Life, though at first glance it appears to contain very rich health-related content. The other main shortcomings of Second Life relate to a lack of activity, a low number of resource users, problems with Second Life's search features, and the difficulty of finding trustworthy information. ConclusionsFor the average user, Second Life offers very little unique value compared to other online health resources.